Relations of the United States with Individual Selected Countries of the Middle East during the Presidency of Donald Trump (2017–2021) - Kania , Jakub (Vade Nobiscum, tom XXIV/2024: Studia nad Bliskim Wschodem, 2024)
The Middle East is a special place on the world map. In international relations, the countries of this region are either the object or subject of the foreign policy of the major powers, including, naturally, the United States. A particularly interesting period in the history of international relations was the 2017–2021 term of office of the U.S. President Donald Trump. He dramatically changed the country’s foreign policy leading to partial isolationism and a reduction in aid to individual partners, especially those in Europe. In my article, I will focus on the White House occupantʼs administrationʼs relations with individual Middle Eastern countries. I will answer the question of whether they were subjects or objects in Washingtonʼs eyes. Relations with the countries they presented on the basis of an analysis of relations between the US and individual countries, which I list below. The presentation, due to the large number of countries, will include individual Arab countries such as Iraq, Iran, Saudi Arabia, Afghanistan, Syria. The close relationship between the US and Israel, which influenced the aforementioned power centers, will also be discussed. Certain decisions and events were influential, and aroused interest in other countries and other parts of the world. This demonstrates the seriousness and importance of U.S.’ relations with other Middle Eastern countries. They became particularly interesting because of the discontinuation of the predecessors’ policies and Trump’s administrationʼs introduction of the America First doctrine, which was also felt by Middle Eastern countries. Whether interstate contacts were the rule, bound by a geographic or religious key, or whether the policy was quite different for each individual player, also became the subject of the study. My presentation is based on texts on: The United States, President Donald Trump and the policies, especially foreign policy pursued by him. The articles and monographs describing the situation in the Middle East in 2017–2021 will also be relevant.